Pengaruh Leverage Operasi, Leverage Keuangan, dan Karakteristik Perusahaan terhadap Risiko Sistematik Saham: Studi Empirik pada Emiten Sektor Pertambangan di Bursa Efek Indonesia - Bram Hadianto; Lauw Tjun Tjun (Universitas Kristen Maranatha, 2009)
Systematic risk or beta is a risk that considered by investor as relevant risk in investing stock. Therefore, factors that influence beta remark important. The aim of this research is to know the impact of operating leverage, financial leverage, and firm’s characteristic on the systematic risk of mining sector stocks. Firm characteristic is proxied by qualitative dummy variable with two categories. First category consists of LQ45 index constituent mining companies and the second is excluding group of LQ45 index constituent mining companies. This research employs ANCOVA model with pooled data. The result states that operating leverage and the financial leverage have no impact on systematic risk. Firm characteristic is positively impact on systematic risk. In other words, the systematic risk of LQ45 index constituent mining companies group is higher than the excluding group of LQ45 index constituent mining companies. Keywords: Systematic risk, Firm characteristic.